Review of mifamurtide in the treatment of patients with osteosarcoma - Leo Kager; Ulrike Pötschger; Stefan Bielack (Dove Medical Press, 2010)
Leo Kager1, Ulrike Pötschger2, Stefan Bielack31St. Anna Children’s Hospital, Vienna, Austria; 2Children’s Cancer Research Institute, Vienna, Austria; 3Klinikum Stuttgart, Olgahospital, Pediatrics 5 – Oncology, Hematology, Immunology, Stuttgart, GermanyAbstract: Osteosarcoma is the most common primary malignant tumor of bone. The disease, however, is very rare with less than 2,000 expected patients at all age groups per year within the European Union and the United States of America. With multimodal therapy, which combines multiagent chemotherapy and complete resection of all macroscopically detectable tumors, about 60%–70% of patients with localized osteosarcoma can be cured. The prognosis, however, is still poor for patients with synchronous or metachronous metastatic or nonresectable primary disease, with reported 5-year event-free survival (EFS) rates of less than 30%. Overall, the EFS rate has been rather stable since the introduction of combination chemotherapy including doxorubicin, cisplatin, high-dose methotrexate with leukovorin rescue, and/or ifosfamide. Mifamurtide, a modulator of innate immunity, which activates macrophages and monocytes, which in turn release chemicals with potential tumoricidal effects, may help to control microscopic metastatic disease and has been safely given together with standard adjuvant chemotherapy to patients with high-grade osteosarcoma. Results of the recently published intergroup study 0133 trial from the Children’s Cancer and Pediatric Oncology Groups suggest that mifamurtide is a medicine that deserves further investigation in this orphan disease.Keywords: orphan drug, orphan disease, outcome innate immunity, immunotherapy